2017
DOI: 10.1186/s13014-017-0893-x
|View full text |Cite
|
Sign up to set email alerts
|

Combined high dose radiation and pazopanib in metastatic renal cell carcinoma: a phase I dose escalation trial

Abstract: BackgroundThe primary objective was to determine maximum tolerated radiation dose in patients with metastatic renal cell carcinoma on pazopanib treatment.MethodsTreatment-naïve patients received pazopanib according to standard of care. Stereotactic body radiotherapy (SBRT) was delivered concurrently to the largest metastatic lesion at day 8, 10 and 12. SBRT doses were escalated in 3 dose levels (24 Gy/3, 30 Gy/3 and 36 Gy/3). Dose level was assigned using Time-to-Event Continual Reassessment Method with the ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…The studies on extracranial mRCC are not conclusive about the potential benefit of adding SRT to target therapy. In a recent phase I/II study including 13 patients treated with Pazopanib and SBRT local control and response rates outside the radiation field were good but seemed not to be superior when compared to SBRT or Pazopanib in monotherapy [52]. Contrarily, Dengina et al [53] observed in a small phase 1b Volga Study (VEGFR inhibitor or mTOR inhibitor or checkpoint inhibitors and SRT) that the difference in response in the target and control metastases evaluated by a mean size of the lesions before and at 2 months after SBRT was statistically significant (p < 0.01).…”
Section: Target Therapy and High Doses Rtmentioning
confidence: 96%
“…The studies on extracranial mRCC are not conclusive about the potential benefit of adding SRT to target therapy. In a recent phase I/II study including 13 patients treated with Pazopanib and SBRT local control and response rates outside the radiation field were good but seemed not to be superior when compared to SBRT or Pazopanib in monotherapy [52]. Contrarily, Dengina et al [53] observed in a small phase 1b Volga Study (VEGFR inhibitor or mTOR inhibitor or checkpoint inhibitors and SRT) that the difference in response in the target and control metastases evaluated by a mean size of the lesions before and at 2 months after SBRT was statistically significant (p < 0.01).…”
Section: Target Therapy and High Doses Rtmentioning
confidence: 96%
“…Acute and late grade 3 toxicity was reported in 1.7% and 2.9% of patients, respectively. 70 Finally, radiation may be used as an adjunct to surgical metastasectomy. Local control rates at 12 and 24 months were 100% versus 62% and 93.4% versus 35.3% for SRS and EBRT, respectively; however, the limited sample size precluded multivariable analysis to identify features that were associated independently with local control.…”
Section: Radiation Therapymentioning
confidence: 99%
“…A recent phase 1 dose-escalation study (clinicaltrials.gov identifier NCT02334709) combined SRS to the largest metastatic lesion in 13 patients who had mRCC with pazopanib, and the combination produced a 1-year local control rate of 83% and a 1-year PFS rate of 28%. 70 Finally, radiation may be used as an adjunct to surgical metastasectomy. Paly and colleagues reported on a multi-institutional cohort of 98 patients who received intraoperative radiation therapy at the time of RCC resection, including 71 who underwent resection of locally recurrent RCC.…”
Section: Radiation Therapymentioning
confidence: 99%
“…Miller reported similar, limited toxicity in 101 RCCpatients treated with single fraction SBRT with or without TKI [33]. In a phase I dose escalation trial, no dose limiting toxicities occurred in 13 RCC-patients treated with hypofractionated SBRT and pazopanib [67]. Several case reports have however been published concerning toxicities of combination strategies [68][69][70].…”
Section: Combination Therapymentioning
confidence: 99%